The Hidalgo and his avatars: The subway as cultural space of Mexico City - Serna Luna, Erick (Universidad Nacional de Colombia - Sede Bogotá - Facultad de Artes - Instituto de Investigaciones Hábitat, Ciudad & Territorio, 2021)
This article talks about the historical process of transformation in the Hidalgo´s subway station. The purpose is to show how the culture plays a political role in the conformation and transmission of a particular perspective about the city. The description of each one of the phases of the transformation process of the Hidalgo´s subway station shows how the urban politic of renovation and recovery of public spaces in Mexico City has been extended to the subway. In this context is framed the great exposition Involuntary, inaugurated in the Hidalgo station as part of the 50th anniversary of the subway of Mexico City. Due to the artistical perspective of the exposition and due to the institutional discourses of promotion, Involuntary represents a cultural perspective that has no rapport with the social activities of the people which have created their identity in relationship with the station’s space. In consequence, Involuntary is an example of the lack of citizen’s inclusion in the cultural politics of appropriation of public spaces, politics that have been a means by which government authorities promote and build their vision of the city.